Comparing the context of immigrant homicides in Miami : Haitians, Jamaicans and Mariels - Lee, M. T.; Martínez Junior, R.
tbls.
pp. 794-812
Keywords: Inmigrantes; Homicidio; Estados Unidos de America; Miami; Haitianos; Jamaiquinos; Cubanos